Wound healing in Mac‐1 deficient mice. Issue 3 (27th April 2017) - Chen, Lin; Nagaraja, Sridevi; Zhou, Jian; Zhao, Yan; Fine, David; Mitrophanov, Alexander Y.; Reifman, Jaques; DiPietro, Luisa A.
Abstract: Mac‐1 (CD11b/CD18) is a macrophage receptor that plays several critical roles in macrophage recruitment and activation. Because macrophages are essential for proper wound healing, the impact of Mac‐1 deficiency on wound healing is of significant interest. Prior studies have shown that Mac‐1 −/− mice exhibit deficits in healing, including delayed wound closure in scalp and ear wounds. This study examined whether Mac‐1 deficiency influences wound healing in small excisional and incisional skin wounds. Three millimeter diameter full thickness excisional wounds and incisional wounds were prepared on the dorsal skin of Mac‐1 deficient (Mac‐1 −/− ) and wild type (WT) mice, and wound healing outcomes were examined. Mac‐1 deficient mice exhibited a normal rate of wound closure, generally normal levels of total collagen, and nearly normal synthesis and distribution of collagens I and III. In incisional wounds, wound breaking strength was similar for Mac‐1 −/− and WT mice. Wounds of Mac‐1 deficient mice displayed normal total macrophage content, although macrophage phenotype markers were skewed as compared to WT. Interestingly, amounts of TGF‐β1 and its downstream signaling molecules, SMAD2 and SMAD3, were significantly decreased in the wounds of Mac‐1 deficient mice compared to WT. The results suggest that Mac‐1 deficiency has little impact on the healing of small excisional and incisional wounds. Moreover, the findings demonstrate that the effect of single genetic deficiencies on wound healing may markedly differ among wound models. These conclusions have implications for the interpretation of the many prior studies that utilize a single model system to examine wound healing outcomes in genetically deficient mice.